First report of the causal agent of vine crown gall in Mendoza, Argentina - D’Innocenzo, Sandra; Diaz, Mariano Emanuel; Escoriaza, Maria Georgina (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2024)
Crown gall is one widespread grapevine disease worldwide, caused by Allorhizobium vitis (syn. Agrobacterium vitis) and Agrobacterium tumefaciens (syn. Rhizobium radiobacter). All. Vitis, is the predominant species and primary cause of the disease. This study aimed to identify and characterize molecularly the agrobacteria in plants with crown gall symptoms in Mendoza vineyards. Diseased plants with trunk-based galls were sampled from different areas of Mendoza. Two multiplex PCRs were performed for bacterial identification and characterization, demonstrating that 91.6% of the strains obtained were agrobacteria (77% A. tumefaciens and 23% All. vitis). Fifty percent of All. vitis and 16% of A. tumefaciens identified strains were pathogenic. Pathogenicity tests were also conducted on Kalanchoe daigremontiana, with resulting tumorigenic symptoms. Highlights: Crown gall is one widespread grapevine disease in the world, caused by Allorhizobium vitis (syn. Agrobacterium vitis) and Agrobacterium tumefaciens (syn. Rhizobium radiobacter). This study aimed to identify and characterize molecularly the causal agent of crown gall in Mendoza vineyards. One hundred and forty-eight symptomatic plants were collected from various vine-growing areas of Mendoza. Allorhizobium vitis and Agrobacterium tumefaciens strains were molecularly identified as pathogenic and octopine/nopaline type. All vitis is the predominant pathogenic species in grapevines studied in Mendoza.